A Structured Distributional Semantic Model for Event Co-reference - Goyal, Kartik; Jauhar, Sujay Kumar; Li, Huiying; Sachan, Mrinmaya; Srivastava, Shashank; Hovy, Eduard (Proceedings of the 51st Annual Meeting of the Association for Computational Linguistics (ACL 2013), 2013)
In this paper we present a novel approach to modelling distributional semantics that represents meaning as distributions over relations in syntactic neighborhoods. We argue that our model approximates meaning in compositional configurations more effectively than standard distributional vectors or bag-of-words models. We test our hypothesis on the problem of judging event coreferentiality, which involves compositional interactions in the predicate-argument structure of sentences, and demonstrate that our model outperforms both state-of-the-art window-based word embeddings as well as simple approaches to compositional semantics previously employed in the literature.